No water to waste, not even wastewater - Keraita, Bernard N. (Technical Centre for Agricultural and Rural Cooperation, 2002)
With competition stiff for high quality fresh water for domestic and industrial users, the use of wastewater for agriculture can release better quality water for these other sectors. Wastewater unquestionably contains valuable nutrients, but poses...